You are on page 1of 9

1

Assignment 6 — Solutions 3/4/04

Problem 4.1

(a)

dHq£ - p ê 2L ij dHf£ L dHf£ - p ê 2L dHf£ - 3 p ê 2L y
rHx” £ L = q dHr£ - aL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
dHf£ - pL
k r sin q {
ӣL
r r sin q r sin q r sin q
qlm = ‡ 3 x£ Ylm * Hq£ , f£ L r£l rHx

ÄÅ É
ÅÅ * p
Å ij p 3 p yzÑÑÑÑ
= q a ÅÅYlm J ÅÅÅÅÅ , 0N - Ylm J ÅÅÅÅÅ , pN + Ylm J ÅÅÅÅÅ , ÅÅÅÅÅ N - Ylm j ÅÅÅÅÅ , ÅÅÅÅÅÅÅÅÅÅ zÑÑ
ÅÇ k 2 2 {ÑÖ
l * p * p p *
2 2 2 2

From the math handbook:

l
o 2 l + 1 Hl + m - 1L!! Hl - m - 1L!!
o
o 2 ‰Â m f $%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%% %%%%%%%%%%%%%%%% %%%%%%%%%%%%%%%%
o ÅÅÅÅÅ H-1L ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ%ÅÅÅÅ%%%%ÅÅ% , l + m even
Ylm = m
o Hl + mL!! Hl - mL!!
1 l+m
ÅÅÅÅ
o
o
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
o
p
n0
2
, otherwise

Everything factors out front except the f dependence:

‰-Â m p = H-1Lm
‰- m pê2 = I‰Â pê2 M = Â-m = H-ÂLm
-m

‰-3  m pê2 = I‰Â pê2 M-3 m = Â-3 m = H-ÂLm
l
o0
‰0 - ‰-Â m p + ‰-Â m pê2 - ‰-3 Â m pê2 = 1 - H-1Lm + H-ÂLm - Âm = m
o 2 - 2 Â H-1Lk , m = 2 k + 1
, m =2k
n
* 's to be nonzero) unless l is also odd. There-
We see that l + m will be odd (since m must be odd for the sum of Ylm
fore the only nonzero qlm are

2 l + 1 Hl + m - 1L!! Hl - m - 1L!!
qlm = H-1L ÅÅÅÅÅÅÅÅ 2ÅÅÅÅÅ N $%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
2 ÅÅÅÅ J1 - Â H-1L ÅÅÅÅÅÅÅÅ %%%%%%%%%%%%%%%% %%%%%%%%%%%%%%%% %ÅÅÅÅ%%%%ÅÅ% q al , l and m both odd
Hl + mL!! Hl - mL!!
l+m m-1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
p

In particular up to l = 3 the nonzero ones are

q1,≤1 = HÂ ¡ 1L $%%%%%%%%%
3
ÅÅÅÅÅÅÅÅÅÅ q a
2p

q3,≤1 = -HÂ ¡ 1L $%%%%%%%%
ÅÅÅÅÅÅÅÅÅÅÅÅ%Å%%Å% q a3 , q3,≤3 = -HÂ ≤ 1L $%%%%%%%%
ÅÅÅÅÅÅÅÅÅÅÅÅ%Å%%Å% q a3
21 35
16 p 16 p
2

(b)

i dHq£ L dHf£ L dHq£ - pL dHf£ L dHq£ L dHf£ L y
rHx” £ L = q jjdHr£ - aL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + dHr£ - aL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - 2 dHr£ L ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz
k r r sin q {
” £ L = q al @Y * H0, 0L + Y * Hp, 0L - 2 d Y * H0, 0LD
r r sin q r r sin q
* Hq£ , f£ L r£l rHx
qlm = ‡ 3 x£ Ylm lm lm l0 0m

l
o
o
o
o $%%%%%%%% %%%%%%%
ÅÅÅÅ Pl H1L = $%%%%%%%% %%%%%%%
Ylm H0, fL = m Ylm Hp, fL = H-1Ll Ylm H0, fL
2l+1 2l+1
o
o
o
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ , m = 0
o
n0
4 p 4 p
, otherwise

* H0, 0L = Y * Hp, 0L. Thus the only nonzero q are
Note that the dl0 term in qlm kills everything l = 0 since Y0m 0m lm

l
o
o
o
$%%%%%%%% % %%%%%% o q al $%%%%%%%% %%%%%%%
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ A1 + H-1L E = m
2l+1
o
o
2l+1
o
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅ , l even and l > 0
o
ql0 = q al l

n0
4p p
, otherwise

q20 = $%%%%%% è!!!
5 3 4
ÅÅÅÅÅ a2 q , q40 = ÅÅÅÅÅÅÅÅ
ÅÅÅÅÅ a q
p p

(c)

qlm Ylm Hq, fL
FHx” L = ÅÅÅÅÅÅÅÅ ‚ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
1
e0 l,m 2 l + 1 rl+1

Yl0 Hq, fL FHr, q=pê2L+H1êr5 L
ÅÅÅÅÅÅÅÅÅÅÅÅ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
= ÅÅÅÅÅÅÅÅÅè!!! è!!!!!!!! !!!!!ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
q al
ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
e0 p 2l+1 rl+1
l >0,even
r
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ P2 l Hcos qL

q a2 l a
2 p e0 r2 l+1

i 1 y
l=1

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ P2 Hcos qL + jj ÅÅÅÅÅÅÅÅ zz
a2
q
k r5 {
q ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2 p e0 r3 2pea

i 1 y
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ I3 cos2 q - 1M + jj ÅÅÅÅÅÅÅÅ zz
a2
k r5 {
q
2 p e0 r3

(d) With r the radial distance from the origin in the x-y plane:
3

ij 2y
FHx” L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅ zzz
è!!!!!!!! ! !!!!! ! è!!!!!!!! ! !!!!! !
q 1 1 +q r 2 + a2
4 p e0 k r2 + a2 r{
q i 1y
r2 + a2

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ!ÅÅ - ÅÅÅÅÅ zzz
-2q r
è!!!!!!!! ! !!!!!
1
2 p e0 k r2 + a2 r{
ÅÅÅÅÅÅÅÅ
+q r 2 + a2

FHr, q=pê2L
r
a

è!!!
I 2 - 2M q
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4pea

Of course they look the same to the eye...

Problem 4.5

(a) The quantities with superscript (0) belong to the external field. The force on the charge distribution r Hx” L
due to the external electric field is

÷” ÷ ”H0L
F = ‡ 3 x rHx” L E Hx” L

÷ ”H0L ÷”
field vary slowly over the distribution, we can Taylor expand E about x” = 0 (using summation notation):
Choose coordinate systems so that the chages are localized near the origin. Since the potential and thus the electric

÷” ÄÅ÷ ” ÷” ÷ ”H0L ÷” ÷ ”H0L ÷” ÉÑ
Å H0L Ñ
F = ‡ 3 x rHx” L ÅÅÅÅE H0 L + xi ∑i E H0L + ÅÅÅÅÅÅÅÅÅ xi x j ∑i ∑ j E H0 L + …ÑÑÑÑ
ÅÇ ÑÖ
1

÷ ”H0L ÷” ÷ ”H0L ÷” ÷ ”H0L ÷”
= J‡ 3 x rHx” LN E H0 L + J‡ 3 x xi rHx”LN ∑i E H0 L + ÅÅÅÅÅ J‡ 3 x 3 xi x j rHx” LN ∑i ∑ j E H0L + …
2!
1
6

We recognize the first integral as the total charge q and the second as the ith component of the dipole moment ÷p” .
÷ ” ÷ ”H0L ÷ ”H0L
Using the 6th vector formula on the front cover of Jackson, “ ä E = 0, and the fact that E is an external field:

÷ ” ÷ ” ÷” ÷ ” ÷ ” ÷” ÷” ÷ ” i rext y ÷” ÷”
0 = “ äI“ ä EM = “ I“ ÿ EM - “2 E = “ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ zz - ∑i ∑i E = -∑i ∑i E = 0
k e0 {
÷ ”H0L ÷ ”H0L
thus we can gratuitously add r2 di j ∑i ∑ j E ∂ ∑i ∑i E = 0 to the third integral:
4

÷” ÷ ”H0L ÷” ÷ ” ÷ ”H0L ÷” ÷ ”H0L ÷”
F = q E H0L + ÷p” ÿ “ E H0L + ÅÅÅÅÅ J‡ 3 x A3 xi x j rHx” L - r2 di j EN ∑i ∑ j E H0L + …
1
6

÷ ” ÷ ”H0L
“ ä E = 0, and the fact that ÷p” is a constant:
Now the remaining integral looks like the traceless quadrupole moment tensor Qi j . Using the 9th vector formula,

÷” ÷ ”H0L ÷ ” ÷” ÷” ÷” ÷ ” ÷” ÷” ÷” ÷ ” ÷”
“ I÷p” ÿ E M = ÷p” ÿ “ E H0L + EH0L ÿ “ ÷p” + ÷p” äI“ ä E H0L M + EH0L äI“ ä ÷p”M = ÷p” ÿ “ EH0L
÷” ÷ ”H0L ÷” ÷ ” ÷ ”H0L ÷” ÷ ”H0L ÷”
F = q E H0 L + “ A÷p” ÿ E H0 LE + ÅÅÅÅÅ Qi j ∑i ∑ j E H0 L + …
1

÷”
6

One more to go. Define the vectors ÷a”i and bi (here the i's are to be thought of as labels) to have components
Ha÷” L ª Q and ÷b” ª ∑ ÷E”H0L ñ Hb÷” H0L
i L j ª ∑i E j respectively. Now use the 9 vector formula again, together with
÷ ” ÷ ”H0L ÷ ” ÷” ÷ ” ÷ ”H0L ÷ ” ÷ ”H0L
“ ä E = 0 [so “ ä bi = “ äI∑i E M = ∑i I“ ä E M = 0] and the fact that Qi j is constant (thus so is ÷a”i ):
th
i j ji i i

÷” H0L ÷ ” ÷” ÷” ÷” ÷ ” ÷” ÷” ÷ ” ÷” ÷” ÷ ” ÷” ÷” ÷ ” ÷”
“ IQi j ∑ j Ei M = “ Ia j ÿ b j M = Ia j ÿ “M b j + Ib j ÿ “M a j + a j ä I“ ä b j M + b j ä I“ ä a j M
÷ ” ÷”
÷” ÿ “ ÷ ”H0L
= Ia j M b j = HQi j ∑i L ∑ j E

÷”
We recognize the last as the third term of F (up to a 1 ê 6). So

÷” ÷ ”H0L ÷” ÷ ” ÷ ”H0L ÷” ÷” i 1 H0L ÷” y
F = q E H0L + “ A÷p” ÿ E H0 LE + “ jj ÅÅÅÅÅ Qi j ∑ j Ei H0 Lzz + …
k6 {
÷”
÷”
because as Jackson says W is a constant. However you can use the definition W = Ÿ¶0 F ÿ x” with the same method
which is precisely what Jackson has. As for the relation to 4.24, you can't take the gradient and equate it to F

÷ ”H0L ÷ ”
of expanding E in F and get the same result.

(b)

÷÷” ÷” ÷ ”H0L ÷” ÷ ”H0L ÷”
N = ‡ 3 x x” äArHx” L E E = ‡ 3 x x” äArHx” L IE H0 L + xi ∑i E H0 L + …ME

÷ ”H0L ÷” ÷”
= J‡ 3 x x” rHx” LNä E H0 L + ‡ 3 x rHx” L x` j e jkl xk xi ∑i ElH0L H0 L + …

÷ ”H0L ÷” ÷”
= ÷p” ä E H0L + ÅÅÅÅÅ J‡ 3 x A3 xk xi rHx” L - r2 dki EN x` j e jkl ∑i ElH0L H0 L + …
1

÷ ” ÷ ”H0L
3

The r2 piece we've added is the integral of x` j e jkl ∑k ElH0L = “ ä E = 0, so we're good. Also from the vanishings
÷ ” ÷ ”H0L
of the components of “ ä E = x` i ei jk ∑ j Ek = x` i ei jk H∑ j Ek - ∑k E j L ê 2 = 0 we see that ∑ j Ek = ∑k E j . Thus

÷÷” ÷ ”H0L ÷” H0L ÷” ÷ ”H0L ÷” H0L ÷”
N = ÷p” ä E H0L + ÅÅÅÅÅ x` j e jkl Qki ∑i El H0 L + … = ÷p” ä E H0L + ÅÅÅÅÅ x` j e jkl ∑l AQki Ei H0 LE + …
1 1
3 3

You can easily compute, say, N1 and see that the same as given by Jackson.
5

Problem 4.6

Q ª Qzz ê e , Qxx = Q yy = -Qzz ê 2 , Qi j = 0 otherwise
÷”
(a) Choose a coordinate system so that the nucleus is centered at the origin. Since E is an external field:

÷ ” ÷”
0 = I“ ÿ EM0 = H∑x Ex + ∑ y E y + ∑z Ez L0 ï H∑x Ex + ∑ y E y L0 = -H∑z Ez L0

W = - ÅÅÅÅÅ Qi j H∑i E j L0 = - ÅÅÅÅÅ HQxx ∑x Ex + Q yy ∑ y E y + Qzz ∑z Ez L0
1 1

1 i Qzz y i 1 y
= - ÅÅÅÅÅ jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ H∑x Ex + ∑ y E y L + Qzz ∑z Ez zz = - ÅÅÅÅÅ Qzz jj- ÅÅÅÅÅ H-∑z Ez L + ∑z Ez zz
6 6

6 k 2 {0 k 2 {0
1
6
= - ÅÅÅÅÅ Q H∑z Ez L0
e
4

(b)

ij 4 W 4 p e0 a30 yz
H∑z Ez L0 = - ÅÅÅÅÅÅÅÅÅÅÅÅÅ = jjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4W e
k Qe { 4 p e0 a0
Qe e 3

ji 4 H107 ê sL 4 p H8.85ä10-12 C 2 ê N ÿ m2 L H0.529ä10-10 mL zyz
º jjjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
3

k H2ä10
-28 m2 L H1.60ä10-19 CL2
e
{ 4 p e0 a0
ÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
3
e
º -0.0853 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4 p e0 a30

(c) For a nucleus of total charge Z e and constant charge density r = Z e ê V where V is the volume of the
spheroid:

è!!!!!!!!!2!!!!!!!!
!
1-z êa2
z
V = ‡ v f ‡ z ‡
2p a b ϖ = b 1− z2 / a2
v

b2 i z2 yz i a3 yz
-a z
z ÅÅÅÅÅÅÅÅÅ jjjj1 - ÅÅÅÅÅÅÅÅÅ zzz = 2 p b2 jjjja - ÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz
0 0

= 4p‡
a

0 2 k a2 { k 3 a2 { ϖ
4
= ÅÅÅÅÅ p a b2 ϖ 2 z2
3 + =1
b2 a 2

è!!!!!!!!!2!!!!!!!!
!
1-z êa2
Qzz = ‡ 3 x I3 z2 - r2 M r = r ‡ v f ‡ z ‡ v A3 z2 - Iz2 + v2 ME
2p a b

ÄÅ É b è!!!!!!!!
2 !!!!!2!
ÅÅ 2 2 v4 ÑÑÑ ÅÅÅÅaÅ a -z
-a

ij 2 2y
0 0

= 4 p r ‡ z ÅÅÅz v - ÅÅÅÅÅÅÅÅÅÅ ÑÑÑ
Å Ñ = 4 p r ‡ z jjz
j ÅÅÅÅÅÅÅÅÅ Ia2 - z2 M - ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅ Ia2 - z2 M zzzz
ÅÅÇ 4 ÑÑÖ0
a a b2 1 b4
0 0 k a2 4 a4 {
6

ÄÅ É
ÅÅ ij b4
Å b2 yz 4 ij b4 yz 2 b4 ÑÑÑÑ
j z j z
= 4 p r ‡ z ÅÅÅ- jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ zz z + jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + b zz z - ÅÅÅÅÅÅÅÅÅ ÑÑÑ
ÅÅÇ k 4 a4 4 ÑÑÖ
a

a2 { k 2a {
2

Ä ÉÑa
p b2 r ÅÅÅÅ ÑÑ
0 2

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅ-I4 a + b M ÅÅÅÅÅÅÅÅ + I4 a + 2 a b M ÅÅÅÅÅÅÅÅ - a b zÑÑÑÑ
a4 ÅÅÇ ÑÑÖ0
2 2 z5 4 2 2 z3 4 2

p b2 r i 4 a7 y jij ÅÅÅÅÅÅÅÅ 8 a5 b2 zy
5 3

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - a4 b2 azzzz = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz
a5 b2 4 a7 2 a5 b2 p b2 r 8 a7
a4 k 5 5 3 3 { a4 k 15 15 {

= ÅÅÅÅÅÅÅÅÅÅ r a b2 Ia2 - b2 M
8p
15

Q = Qzz ê e = ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ a b2 Ia2 - b2 M ë e = ÅÅÅÅÅ Z Ia2 - b2 M
8p
15 4 p a b ê 3
Ze 2
2 5

With R = Ha + bL ê 2:

Q = ÅÅÅÅÅ Z Ha + bL Ha - bL = ÅÅÅÅÅ Z R Ha - bL
2 4

5 H2.5ä10-28 m2 L
5 5
a-b
4 H63L H7ä10-15 mL2
5Q
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º 0.101
R 4 Z R2

Problem 4.7

(a)

rHr”L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ r2 ‰-r sin2 q
1
64 p
qlm = ‡ 3 x Ylm ”L =
* Hq, fL rl rHx * Hq, fL rl ÅÅÅÅÅÅÅÅ
‡ r ‡ r q ‡
¶ p 2p 1 2 -r 2
r sin q f Ylm ÅÅÅÅÅÅ r ‰ sin q
64 p
2 l + 1 Hl - mL! 1
0 0 0

= $%%%%%%%%%%%%%%%%
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ %ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
%%%%%%%%%%%%%%%%
ÅÅÅÅÅÅÅÅÅ% ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ r rl+4 ‰-r ‡ f ‰-Â m f ‡ u I1 - u2 M Pl HuL
¶ 2p

4 p Hl + mL! 64 p 0
1

0 -1

i 1y
= ÅÅÅÅÅÅÅÅÅÅÅÅÅ $%%%%%%%% ÅÅÅÅ Hl + 4L! ‡ u jj1 - ÅÅÅÅÅ P2 HuL - ÅÅÅÅÅ zz Pl HuL
%%%%%%%
dm0 2l+1
k 3{
1 2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
64 4p -1 3

= ÅÅÅÅÅÅÅÅÅÅÅÅÅ $%%%%%%%% %%%%%%%
ÅÅÅÅ Hl + 4L! ‡ u @P0 HuL - P2 HuLD Pl HuL
dm0 2l+1 1
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
96 4p -1

i y
= ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅ $%%%%%%%% ÅÅÅÅ Hl + 4L! jj2 dl0 - ÅÅÅÅÅ dl2 zz
%%%%%%%
1 dm0 2l+1
k {
2
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4 4! 4p 5

The only nonzero moments are

ÅÅÅÅÅÅÅÅÅÅ , q20 = -3 $%%%%%%
è!!!
1 5
q00 = ÅÅÅÅÅÅÅÅ ÅÅÅÅÅ
2 p p
7

At large distances:

F> Hx” L = ÅÅÅÅÅÅÅÅ ‚ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ r-l-1 Ylm Hq, fL
1 qlm
e0 l,m 2 l + 1

jij 1 zy
jj ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ P0 Hcos qL - 3 è!!! ÅÅÅÅÅÅÅÅÅÅ P2 Hcos qLzzzz
5 ÅÅÅÅÅÅÅÅÅÅÅÅÅ $%%%%%%%%%
è!!!ÅÅÅÅÅÅÅÅÅÅÅÅÅ j 2 r è!!!!!!!
1 1 1 5

k {
= ÅÅÅÅÅÅÅÅ
p e0 4p 5 r3 4p
1 i1 y
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅ P0 Hcos qL - ÅÅÅÅÅÅÅÅ P2 Hcos qLzz
4 p e0 k r {
6
r3

(b)

FHx” L = ÅÅÅÅÅÅÅÅ „ ‡ 3 x ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅ rHx” £ L Ylm
* Hq£ , f£ L Y Hq, fL
1 1 rl<
lm
e0 2l+1 r>l+1
l,m

The angular integrals are the same as in (a). The radial integral now splits into two:

Rl HrL ª ‡ r£ ÅÅÅÅÅÅÅÅ<ÅÅÅÅÅ r£4 ‰-r = ‡ r£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‰-r + ‡ r£ rl r£3-l ‰-r
¶ rl £ r r£l+4 £ ¶ £

ÄÅ É
Ñ ÄÅ ÉÑr
ÅÅÅ ÑÑ ÅÅ ÑÑ
0 rl+1
> 0 rl+1 r

1 ÅÅ -r£ Hl + 4L! r Ñ
ÑÑ Å
ÅÅ -r£ H3 - lL! r ÑÑ
Å Ñ Å ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ
r

= ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅ-‰ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑ + r ÅÅ-‰ „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
l+4 3-l
£l+4-k £3-l-k

rl+1 ÅÅÅ Hl + 4 - kL! ÑÑÑ ÅÅ
ÅÅÅ H3 - l - kL! ÑÑÑ
ÇÅÅ ÖÑÑ0 ÑÑÖ0
l

Ç
ij 3-l y
Hl + 4L! r3-k zzzz
k=0 k=0

Hl + 4L! jj H3 - lL! r3-k
j
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‰ jjj„ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - „ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz
l+4

j H3 - l - kL! Hl + 4 - kL! z
-r

k k=0 {
rl+1
k=0

which holds for l § 3 as will be the case since all other qlm 's vanish:

Rl HrL qlm Ylm Hq, fL 1 ij R0 HrL P0 Hcos qL 5 P2 Hcos qL yz
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅ jjjj ÅÅÅÅÅÅÅÅ
FHx” L = ÅÅÅÅÅÅÅÅ ‚ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ $%%%%%% $%%%%%%%%% 2 zzz
HrL z
e0 k 2 p 24 è!!!!!!
Åè!!! !
e0 l,m H2 l + 1L Hl + 4L!
1 5

{
ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å - 3 ÅÅÅÅ
Å ÅÅÅÅ
Å ÅÅÅ
Å Å ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅ
Å ÅÅÅ
Å R
4p p 4 p 720

i y
= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjP0 Hcos qL R0 HrL - ÅÅÅÅÅ P2 Hcos qL R2 HrLzz
96 p e0 k {
1 1
5

i y
R0 HrL = ÅÅÅÅÅÅÅÅÅ + ‰-r jj-18 - ÅÅÅÅÅÅÅÅÅ - 6 r - r2 zz
k {
24 24

i y
R2 HrL = ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‰-r jj-120 - ÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅ - 30 r - 5 r2 zz
r r

k {
720 720 720 360

Ä
Å É
i 24 i 24 y Å 144 i 144 yÑÑy
FHx” L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅ - ‰-r jj ÅÅÅÅÅÅÅÅÅ + 18 + 6 r + r2 zz - P2 Hcos qL ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅ - ‰-r jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ + 24 + 6 r + r2 zzÑÑÑÑ
r3 r3 r2 r

96 p e0 k r k r { ÅÇ r3 k r3 {ÑÖ{
1 144 72
r2 r

Expanding in powers of r for r Ø 0, using ‰-r = 1 - r + r2 ê 2 - r3 ê 6 + r4 ê 24 - r5 ê 120 +  Hr7 L:
8

ÄÅ
i 24 i 24 Å 144
y i 24 y
FHx” L = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjjj ÅÅÅÅÅÅÅÅÅ - jj ÅÅÅÅÅÅÅÅÅ + 18 + 6 r + r2 zz + r jj ÅÅÅÅÅÅÅÅÅ + 18 + 6 rzz - jij ÅÅÅÅÅÅÅÅÅ + 18zyz + ÅÅÅÅÅÅÅÅ ijj ÅÅÅÅÅÅÅÅÅ zyz - P2 Hcos qL ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ
ÅÅ r3
r2 r3 24
k r { k r { k r { 6 k r { ÅÇ
1 24
96 p e0 k r
ÅÅÅÅÅÅÅÅ
2

i 144 y i 144 y ij 144
- jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ + 24 + 6 r + r2 zz + r jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ + 24 + 6 rzz - j ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅ
r2
k r { k r { k r3
144 72 144 72 144
ÅÅÅÅÅÅÅÅ
É
r5 i 144 yÑÑÑy
3 r 2 r 3 r 2 r 2 r2
y r i 144 72 y r4 i 144 144 y
+ ÅÅÅÅÅÅÅÅÅ + 24zz + ÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅ zz - ÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ zz + ÅÅÅÅÅÅÅÅÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅ zzÑÑÑÑzzzz + Ir3 M
r2 { 120 k r3 {ÑÑÖ{
3

{ 6 k r3 r { 24 k r3
72 144
r2
i y 1 i1 y
r

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjjj6 - ÅÅÅÅÅÅÅÅ P2 Hcos qL zzzz + Ir3 M = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ jjjj ÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅ P2 Hcos qL zzzz + Ir3 M
1 r2 r2
96 p e0 k 5 { 4 p e0 k 4 120 {

(c)

÷” ” ÷” 1 ÷” i 1 y
EHxL = -“ F Hx” L = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ jjjj ÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅ P2 Hcos qL zzzz + Ir3 M
r2
4 p e0 k 4 {
÷” ÷”
120

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ A3 z2 - Ix2 + y2 + z2 ME + Ir3 M = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ I2 z2 - x2 - y2 M + Ir3 M
1 1

÷”
960 p e0 960 p e0

= ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ H-x x` - y y` + 2 z z` L + Ir3 M
1

1 i y
480 p e0

∑x Ex = ∑ y E y = - ÅÅÅÅÅ ∑z Ez = - ÅÅÅÅÅ jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz , all other ∑i E j = 0
2 k 240 p e0 {
1 1
2

1 i 1 y
‚ Qi j H∑i E j L0 = - ÅÅÅÅÅ jj- ÅÅÅÅÅ Qzz ∑x Ex - ÅÅÅÅÅ Qzz ∑ y E y + Qzz ∑z Ez zz
6 k 2 {0
1 1
W = - ÅÅÅÅÅ
6 i, j 2

H1.60ä 10-19 CL H10-28 m2 L H1.60ä10-19 CL
960 p H8.85ä 10-12 C 2 ê N ÿ m2 L H0.529ä10-10 mL3
e 1
= - ÅÅÅÅÅ Q ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
4 240 p e0

†W § º 6.49ä10-28 J ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º I9.80ä105 HzM h
h
6.63ä10 -34 J ÿs

Problem 4.10

(a) It behooves us to choose a coordinate system with the azimuthal symmetry manifest, e.g. the dielectric in
the z > 0 plane. Working in spherical coordinates, we can expand in Legendre polynomials:

z
l
o ”L =
o
o Hx ‚ IA l + B r-Hl+1L M P Hcos qL , 0 < q < ÅÅÅÅ
o
o

o
p
o
o
FHx” L = m
F> l r l l Å Φ>

o
o
2 -Q

o
ε
o
o F< Hx” L = ‚ ICl rl + Dl r-Hl+1L M Pl Hcos qL , ÅÅÅÅÅ < q < p
l=0

o
ϖ
o

o
p ε0
n
+Q
2
l=0 Φ<
9

Boundary conditions:

∑F> ƒƒ ∑F< ƒƒ
e ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ § = e0 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ
∑q ƒƒq=pê2 ∑q ƒq=pê2
ï l = 0 (derivatives must vanish to be satisfied for all r)

∑F> ƒƒ ∑F< ƒƒ
ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ §ƒ
∑r ƒq=pê2 ∑r ƒq=pê2
B0 D
ï - ÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅ0ÅÅ ï B0 = D0

F> §q=pê2 = F< §q=pê2
r 2 r2
ï A0 = C0

We see that the solution is actually trivial:

FHx” L = A + ÅÅÅÅÅÅ
B
r

We can take A = 0 since we're only interested in the field. The electric displacement in the two regions are

÷÷” ÷” B
D> = -e “ F = -e ÅÅÅÅÅÅÅÅ r`

÷÷” ÷”
r2
B
D< = -e0 “ F = -e0 ÅÅÅÅÅÅÅÅ r`
r2

We can use Gauss' law to fix the constant:

÷÷” `
Q = ® D ÿ n a = 2 p a J-e ÅÅÅÅÅ2ÅÅÅÅ - e0 ÅÅÅÅÅÅÅÅÅ N = -2 B p He + e0 L ï B = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2 p He + e0 L
2 B B Q

÷”
2

÷÷”
a a

2 p He + e0 L r
Q `
E = -“ F = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ2ÅÅÅÅ r

(b)

÷÷”
s> = -e D> ÿ H-r̀L•r=a
eQ
2 p He + e0 L a2
B
= -e ÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ

÷÷”
a 2

s< = -e0 D< ÿ H-r̀L•r=a = -e0 ÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
e0 Q
2 p He + e0 L a2
B
a 2

(c) Using Jackson 4.46:

÷” ÷” Q He - e0 L ÷” Q He0 - eL
P§r=a = He - e0 L E •r=a = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ r` ï spol = -IP - 0M ÿ r` •r=a = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ
2 p He + e0 L a 2 2 p He + e0 L a2